Emotional perception of family-member caregivers regarding the clean intermittent catheterization in myelomeningocele cases - Costa, Regina Célia Villa; Guiotoku, Elizabete Tsubomi Saito; Kravchychyn, Helena; Rocha, Juliana; Carmo, Mariana Magalhães do; Castro, Yara Pisanelli Gustavo (Acta Fisiátrica, 2012)
There are many special needs of the urinary tract of a child with myelomeningocele, who requires constant help from a caregiver who is often a family member that can face doubts, fears, and difficulties related to the clean intermittent catheterization that is necessary in these cases. Objective: This study investigates the thoughts and feelings of family-member caregivers regarding their performing this technique on children, and analyzes how the caregiver feels about the possibility of the child carrying out the procedure him/herself later in life. Method: This observational and transversal research uses both qualitative and quantitative approaches. Also, structured interviews were made and recorded in audio with 15 family-member caregivers from a rehabilitation institution located in the city of São Paulo between April and August of 2012. Lexical and content analyses of the open questions was made using the software SPAD-T® version 1.5. Results: The categories found where: the caregiver’s general impression of the catheterization, how long it took to get used to the procedure, the caregiver’s perception of the child’s general impressions, references to the professional’s intervention, the caregiver’s perception of the auto-catheterization, the caregiver’s perception of how capable the child could be (to conduct the procedure him/ herself), and references to the (in)dependence in the caregiver-child relationship. The statistical analysis was made using the software SPSS® 15.0. Conclusion: All caregivers showed negative feelings and thoughts about the catheterization even though some of them mentioned positive points as well. Moreover, most caregivers could not answer clearly whether the child would perform the self-catheterization by itself in the future.